A register of public-sector research organizations as a tool for research policy studies and evaluation. Issue 4 (24th June 2020) - Lepori, Benedetto
Abstract: This article presents the conceptual and methodological design of a register of public-sector organizations, as well as a preliminary delineation of such organizations in Europe. Conceptual and methodological issues are discussed, as well as the potential usage of the register for interlining datasets and analysis. The significance of the register for research policy and evaluation studies is also discussed, as related with changes associated with New Public Management reforms.